Comparative Assessment of Job Satisfaction Levels among Teachers in Public and Private Secondary Schools in Sierra Leone - George, Tony Patrick; Thulla, Philip Foday Yamba; Massaquoi, Saffa Barbee; Fayiah, Moses (Program Pascasarjana Institut Agama Islam (IAI) Darullughah Wadda'wah Pasuruan, 2025)
This study examined job satisfaction levels among teachers in public and private secondary schools in Sierra Leone. Specifically, the study examined key factors, including salary, workload, working conditions, administrative support, professional development opportunities, and interpersonal relationships. The findings indicate that teachers’ job satisfaction is relatively higher among those aged 36 to 40 compared to those aged 41 and above, who experience the lowest satisfaction. However, there are no significant differences based on professional seniority. Using a mixed-methods approach, data were collected from 380 teachers across various public and private secondary schools in both urban and rural districts. The findings revealed notable differences in job satisfaction between teachers in public and private schools, with public school teachers expressing greater dissatisfaction with salary and promotion prospects. Conversely, private school teachers expressed more concern about job security and workload. Both groups identified poor working conditions, limited professional development opportunities, and insufficient administrative support as significant sources of dissatisfaction. The conclusion is that job satisfaction is vital for teacher retention, motivation, and performance. It is recommended that targeted policy measures and school reforms be implemented to address disparities and improve teachers’ working conditions in both public and private schools, thereby enhancing teacher satisfaction and the quality of secondary education in Sierra Leone.